Endocrine-disrupting activity of mancozeb - Skalny, Anatoly; Aschner, Michael; Paoliello, Monica; Santamaria, Abel; Nikitina, Natalia; Rejniuk, Vladimir; Jiang, Yueming; Rocha, João; Tinkov, Alexey (Archives of Pharmacy, 2021)
The objective of the present study was to review the existing data on the mechanisms involved in the endocrine disrupting activity of mancozeb (MCZ) in its main targets, including thyroid and gonads, as well as other endocrine tissues that may be potentially affected by MCZ. MCZ exposure was shown to interfere with thyroid functioning through impairment of thyroid hormone synthesis due to inhibition of sodium-iodine symporter (NIS) and thyroid peroxidase (TPO) activity, as well as thyroglobulin expression. Direct thyrotoxic effect may also contribute to thyroid pathology upon MCZ exposure. Gonadal effects of MCZ involve inhibition of sex steroid synthesis due to inhibition of P450scc (CYP11A1), as well as 3β-HSD and 17β-HSD. In parallel with altered hormone synthesis, MCZ was shown to down-regulate androgen and estrogen receptor signaling. Taken together, these gonad-specific effects result in development of both male and female reproductive dysfunction. In parallel with clearly estimated targets for MCZ endocrine disturbing activity, namely thyroid and gonads, other endocrine tissues may be also involved. Specifically, the fungicide was shown to affect cortisol synthesis that may be mediated by modulation of CYP11B1 activity. Moreover, MCZ exposure was shown to interfere with PPARγ signaling, being a key regulator of adipogenesis. The existing data also propose that endocrine-disrupting effects of MCZ exposure may be mediated by modulation of hypothalamus-pituitary-target axis. It is proposed that MCZ neurotoxicity may at least partially affect central mechanisms of endocrine system functioning. However, further studies are required to unravel the mechanisms of MCZ endocrine disrupting activity and overall toxicity.
Keywords: Mancozeb; thyroid; testes; ovary; adrenal; adipose tissue